Effect of Adding Sodium Tripolyphosphate on the Physical and Sensory Characteristics of Meatballs Formulated with Dragon Fruit Peel and Oyster Mushroom Blend - Rosmalia, Senarita Septia; Yulistiani, Ratna (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
This study aimed to determine the best addition of Sodium Tripolyphosphate (STPP) to produce chicken meatballs containing dragon fruit peel and oyster mushroom with desirable physical and organoleptic characteristics. The research used a Completely Randomized Design (CRD) with treatments of STPP addition (0%, 0.1%, 0.2%, and 0.3% w/w) with four replications. The data were analyzed using ANOVA and the DMRT test at the 5% level. The results showed that the best treatment was the addition of 0.3% STPP, which produced meatballs with the following characteristics: physical properties (hardness 36.26 N; springiness 0.82; cohesiveness 0.58; chewiness 1333.5), water holding capacity of 71.7%, and organoleptic scores of taste 2.47 (savory), aroma 3.53 (characteristic chicken aroma), and texture 3.73 (chewy). Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and Production